Risk Factors for Outbreaks of Lumpy Skin Disease and the Economic Impact in Cattle Farms of Nakuru County, Kenya - Kiplagat, Samuel Kipruto; Kitala, Philip Mwanzia; Onono, Joshua Orungo; Beard, Philippa M.; Lyons, Nicholas A. (Frontiers in Veterinary Science, 2020)
Lumpy Skin Disease (LSD) is an emerging disease of cattle that causes substantial economic loss to affected regions. However, factors favouring transmission under field conditions and farm-level impacts are poorly quantified. This was a retrospective case-control study of cattle farms in Nakuru, Kenya to determine risk factors associated with lumpy skin disease and the farm-level economic impacts of an outbreak. Data were collected using questionnaires administered through personal interview. Collected data included herd sizes, age and sex structures, breeds, sources of replacement stock, grazing systems and costs (direct and indirect) incurred when LSD outbreaks occurred. Farm-level risk factors were examined through univariable and multivariable logistic regression and a final model built using backward stepwise regression and likelihood ratio tests. The factors associated with LSD outbreaks on univariable analysis included breed (exotic versus indigenous, OR=15.01, P=0.007), source of replacement stock (outside the herd versus within the herd, OR=8.38, P<0.001) and herd size (large [>10 cattle] versus small [1-3 cattle], OR=3.51, P=0.029). In the multivariable logistic regression model, only breed (exotic versus indigenous, OR=14.87, 95% CI 1.94 – 113.97, P=0.009) and source of replacement stock (outside the herd versus within the herd OR=8.7, 95%CI 2.80-27.0, P<0.001) were associated with outbreaks. The economic impact was compared between farms keeping purely indigenous (n=10) or exotic (n=29) breeds of cattle which indicated mean farm-level losses of 7,114 KSH/70USD and 26,965 KSH/267USD respectively. The mean farm-level losses from reduction in milk yield and mortality were estimated at 1,890 KSH/19USD and 621 KSH/6USD for farms keeping indigenous breeds whilst for farms keeping exotic breeds the equivalent losses were 11,275 KSH/112 USD and 9,835 KSH/97USD respectively. The indirect losses from treatments and vaccinations were proportionately much higher on farms with indigenous breeds at 3,715 KSH/37USD making up approximately 53% of the total costs compared to approximately 19% (5,003 KSH/50USD per farm) of the total costs for farms with exotic breeds. These findings indicate that LSD caused significant economic losses at the farm level in Nakuru County. This justifies implementation of disease control measures including quarantine of cattle post-purchase and the need for effective vaccinations of susceptible cattle herds.